Correlation of Ultrasound and histopathology for diagnosis of endometrial cancer in post-menopausal women - Ashraf, Viqar; Imran, Ayesha; Yaqub, Umairah; Chohan, Shazia Firdous (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the usefulness of trans-vaginal ultrasonography for diagnosis of endometrial carcinoma as screening tool by comparing sonographic thickness of endometrium and histopathology in post-menopausal women.Study Design: Quasi-experimental study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan 2024 to Jan 2025.Methodology: After seeking approval of ethical commission, we recruited two Groups of post-menopausal ladies presented with abnormal uterine bleeding, one with normal endometrial thickness and another with abnormal endometrial thickness. We did transvaginal ultrasonography on all patients and performed histopathology of their endometrial tissue taken on biopsy. We compared the frequency of positive cases on histopathology and correlated it to their sonographic findings by calculating sensitivity and specificity to establish diagnostic yield of trans-vaginal ultrasonography in endometrial carcinoma.Results: The sensitivity of trans-vaginal ultrasonography in diagnosis of carcinoma of endometrium was 64.1%, specificity was 92.0%, positive predictive value was 58.6% and negative predictive value was 79.8%. The frequency of carcinoma was 23(35.9%) in Group-A and it was 2(3.3%) in Group-B with p-value of